BehaviourCoach: Exploring the Use of a Web-Based Serious Game in Health Promotion - Fiona Grant; Roushdat Elaheebocus (Serious Games Society, 2024)
Using a multidisciplinary approach, the current study examined the roles of psychological factors and serious games in the promotion of physical activity and wellbeing. The aim was to investigate the use and evaluation of a Web-based application named BehaviourCoach through the following research questions: How do users experience and evaluate this web-application for health promotion? How do elements of serious games and participants' health status relate to intention to use this web-application? Participants (N = 55) engaged with BehaviourCoach for a duration of 45 minutes. Physical activity, psychological wellbeing, user experience, evaluation and intention to use a digital tool for health as well as demographic information were self-reported. On average, participants were sufficiently active as a group to meet the guidelines of 150 minutes per week of activity. They also reported moderate psychological wellbeing. The evaluation of the web application was positive, with participants expressing enjoyment, reporting that they found the game to support social interaction, and that the web application interface's navigation was user-friendly. These factors were found to be positively related to intention to use the digital tool for health promotion in the future. In addition, participants' levels of overall health and subjective wellbeing were predictive of intention to use the web-application for quick results. The study's implications for e-health interventions are discussed, as well as future directions.